Effects of high-K dielectrics with metal gate for electrical characteristics of 18nm NMOS device - Atan N.B.; Ahmad I.B.; Majlis B.B.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper presents a systematic study of various high-K materials on metal gate MOSFET for 18nm NMOS. From the study, we find a suitable combination materials between the high-K and metal gate, which has beneficial effects on the electrical characteristics of 18nm NMOS. The device shows a good improvement on its result of sub-threshold leakage current, IOFF, and drive current, ION for different dielectric constants (k). The virtual design and fabrication of the device were performed by using Athena module. While electrical characteristic performance was simulated by using Atlas module of SILVACO software. Physical models of the 18nm NMOS were used for simulation from Al2O3, HfO2, and TiO2 as the material gate dielectric, with TiSi2 as the metal gate, which provide higher physical thickness that able to reduce the sub-threshold leakage current IOFF. Thus, excellent dielectric properties such as high-K constant, low IOFF, higher ION, threshold voltage VTH, and electrical characteristics were demonstrated. From the simulation results of ION and IOFF, it was proven that HfO2 is the best dielectric material with combination of metal gate, TiSi2. © 2014 IEEE.